Fine Particulate Matter (PM2.5) Promotes CD146 Expression in Alveolar Epithelial Cells and Cryptococcus neoformans Pulmonary Infection - Sun, Zhixiao; Ji, Ningfei; Jiang, Jingxian; Tao, Yuan; Zhang, Enrui; Yang, Xiaofan; Wang, Zhengxia; Chen, Zhongqi; Huang, Mao; Zhang, Mingshun (Frontiers in Microbiology, 2021)
Air pollution is a leading cause of increasing infectious lung diseases. Pulmonary cryptococcosis is a fatal fungal pneumonia in acquired immunodeficiency syndrome patients. In some cases, the pathogen Cryptococcus neoformans also develops dormant nodules in immunocompetent individuals. In the present study, we demonstrated that fine particulate matter (PM2.5) increased CD146 expression in alveolar epithelial cells and promoted Cryptococcus neoformans pulmonary infection. Aryl hydrocarbon receptor (AhR) signaling was required for increased expression of CD146 in epithelial cells treated with PM2.5. In a murine model of pulmonary infection, PM2.5 promoted fungal infection, and CD146 deficiency decreased the fugal burden of Cryptococcus neoformans. Our study may highlight the importance of air pollution to lung mycosis and CD146 as a target for preventing infectious lung diseases.